Real-world functional programming with examples in F♯ and C♯ - Petricek, Tomas (Manning, 2010)
"Functional programming languages like F♯, Erlang, and Scala are attracting attention as an efficient way to handle the new requirements for programming multi-processor and high-availability applications. Microsoft's new F♯ is a true functional language and C♯ uses functional language features for LINQ and other recent advances. Real World Functional Programming is a unique tutorial that explores the functional programming model through the F♯ and C♯ languages. The clearly presented ideas and examples teach readers how functional programming differs from other approaches. It explains how ideas look in F♯-a functional language-as well as how they can be successfully used to solve programming problems in C♯. Readers build on what they know about .NET and learn where a functional approach makes the most sense and how to apply it effectively in those cases. The reader should have a good working knowledge of C♯. No prior exposure to F♯ or functional programming is required."--Resource description page.
Includes bibliographical references (pages 498-500) and index. - Print version record
Keywords: Functional programming (Computer science); F♯ (Computer program language); C# (Computer program language); Programmation fonctionnelle; C# (Langage de programmation); C♯ (Computer program language); C sharp; F sharp; Funktionale Programmierung; Computer Science; Engineering & Applied Sciences